Pemberdayaan Ekonomi Produktif Dalam Penanggulangan Kemiskinan Perdesaan di Kabupaten Rembang - Heryani, Dian; Mardiansjah, Fadjar Hari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
During this time, poverty alleviation program specifically for economic empowerment believed to be succesfull in decreasing the rate of poverty and developing asset. But in fact, it is indicated could not guarantee the poors to come out from their conditions. Because there is uneffectiveness indication in that poverty alleviation, it is needed to observe potential of economic empowerment in rural poverty alleviation. The purpose of this research is to know the potential of economic empowerment including its pattern of the relationship and benefit in rural poverty alleviation in Rembang Regency. Analysis in the research including distribution frequency statistic and descriptive analysis. This research uses 155 samples of economic empowerment beneficiaries of PNPM Mandiri Perdesaan Simpan Pinjam Kelompok Perempuan (credit loan for woman) scattered across the Sub district Bulu and Kaliori as the research areas. Based on the results of the analysis, the economic empowerment in Rembang Regency can not reach out for poverty alleviation in rural areas. It also can not be used as the primary tool in rural poverty alleviation. This is because in program development, most of beneficiaries are coming from un-poors. Besides, their efforts of industry can not reach the poors to come out from the poverty itself. Meanwhile, various obstacles also triggered micro industry of the poors remain marginalized.